PENGARUH PENAMBAHAN BERBAGAI AKTIVATOR DALAM PROSES PENGOMPOSAN SEKAM PADI (Oryza sativa) - Irvan, Permata Mhardela, Bambang Trisakti (Universitas Sumatera Utara, 2014)
Composting process of rice husk (Oryza sativa) by adding various activators have been carried out in LPPM Training Center, University of Sumatera Utara. The purpose of this study was to compare the effect of variation of slurry and bacteria (yeast and EM4) on rice husk composting results. The parameters observed were changes in temperature, water content, C/N ratio, and pH. At the end of the composting results showed that the addition of slurry, yeast and EM4 can lower the temperature and C / N ratio, and with the addition of yeast and 2 liters of slurry can speed up the process of decomposition of compost.